Pola Komunikasi Masyarakat Di Desa Sancang Kabupaten Garut - Nurul Suhartin Hasni; Fardiah Oktariani Lubis; Luluatu Nayiroh (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the verbal and nonverbal communication used in the interaction of the Sancang Village community and to determine the pattern of communication that occurs between members of the Sancang Village community. The method used in this study is a descriptive qualitative method. Data collection techniques used are observation, interviews, documentation and literature studies. Data analysis techniques using data reduction, data presentation and conclusion. The results of the study show that the communication used by the people of Sancang Village is dominantly using verbal communication. With verbal symbols that are often used, namely language. The language used by the people of Sancang Village is using smooth Sundanese and tends to use low intonation. In the procession of taking kaboa trees there are several verbal symbols including: 1. Tawasulan, a prayer ritual that is generally carried out by Muslims to pray for people who have died. 2. Ngidung, is an activity of singing poetry using Sundanese, with the aim of asking permission from the Creator and the owner of the kaboa tree (which is believed by the local community, the owner of the kaboa tree is King Siliwangi) to take the kaboa tree. Nonverbal communication found in the procession of taking kaboa trees is when burning incense. Where the burning of incense has the meaning of conveying a letter to Allah SWT and to the universe to inform that we (who burn incense) have a specific purpose or intention. The communication pattern formed in the communication activities of the Sancang Village community uses two communication patterns, namely, 1. Primary Communication Pattern, the majority of the Sancang Village community communicates face to face through verbal and nonverbal communication. 2. Circular Communication Patterns, the people of Sancang Village routinely hold light discussions almost every day after the sunset call to prayer and use continuous communication patterns to establish good communication. This is done not only to build good communication, but also to build harmony and strengthen relations between the people of Sancang Village. The author uses Symbolic Interaction Theory as the main theory to translate the symbols created as a result of social interactio